Effect of lorcaserin on glycemic parameters in patients with type 2 diabetes mellitus. Issue 5 (27th March 2017) - Magkos, Faidon; Nikonova, Elena; Fain, Randi; Zhou, Sharon; Ma, Tony; Shanahan, William
Abstract : Objective: Lorcaserin, a 5‐HT2C receptor agonist approved for chronic weight management, is also associated with improvements in glycemic parameters in patients with/without type 2 diabetes mellitus (T2DM), but the extent to which these effects are mediated by weight loss is unknown. This post hoc analysis further examines glycemic data from the Phase III BLOOM‐DM study stratified by weight changes. Methods: Patients with T2DM were randomized to lorcaserin 10 mg twice daily or placebo. Glycemic parameters were reported by Week (W) 12 weight loss status ≥5% (Group ≥5%) or <5% (Group <5%). Glycemic parameter changes were analyzed using ANCOVA; the relationship between glycemic parameter changes and percent weight loss was assessed by simple regression modeling. Results: Group ≥5% receiving lorcaserin had greater improvements in fasting plasma glucose (FPG) at W2 (prior to significant weight loss) and greater improvements in glycated hemoglobin (HbA1c) at W12 versus placebo. These improvements were maintained through W52 (FPG, −29.3 mg/dL vs. −24.2 mg/dL; HbA1c, −1.2% vs. −1.1%). Group <5% treated with lorcaserin also had larger decreases in FPG (−28.3 mg/dL vs. −10.0 mg/dL) and HbA1c (−0.8% vs. −0.4%) at W52 versus placebo despite limited weight loss. Conclusions: Lorcaserin may have beneficial effects on glycemic control with or without weight loss.